Appropriateness, endoscopic findings and contributive yield of pediatric gastrointestinal endoscopy - Lee, Way Seah; Zainuddin, Hafizah; Boey, Christopher Chiong Meng; Chai, Pei Fan (Baishideng Publishing Group, 2013)
AIM: To determine the predictability of the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) and American Society for Gastrointestinal Endoscopy (ASGE) guideline with regard to appropriate endoscopic practice in children, positive endoscopic findings and contributive yield in clinical practice. METHODS: This was a descriptive, retrospective analysis, conducted at the Department of Paediatrics, University Malaya Medical Centre, Malaysia. All children who had esophagogastroduodenoscopy (EGD) and colonoscopy from January 2008 to June 2011 were included. An endoscopy was considered appropriate when its indication complied with the NASPGHAN and ASGE guideline. All endoscopic findings were classified as either positive (presence of any endoscopic or histo-logic abnormality) or negative (no or minor abnormality, normal histology); effecting a positive contributive (a change in therapeutic decisions or prognostic consequences) or non-contributive yield (no therapeutic or prognostic consequences). RESULTS: Overall, 76 of the 345 procedures (231 EGD alone, 26 colonoscopy alone, 44 combined EGD and colonoscopy) performed in 301 children (median age 7.0 years, range 3 months to 18 years) had a positive endoscopic finding. Based on the NASPGHAN and ASGE guideline, 99.7 of the procedures performed were considered as appropriate. The only inappropriate procedure (0.3) was in a child who had EGD for assessment of the healing of gastric ulcer following therapy in the absence of any symptoms. The overall positive contributive yield for a change in diagnosis and/or management was 44. The presence of a positive endoscopic finding was more likely to effect a change in the therapeutic plan than an alteration of the initial diagnosis. A total of 20 (5.8) adverse events were noted, most were minor and none was fatal. CONCLUSION: The NASPGHAN and ASGE guideline is more likely to predict a positive endoscopic finding but is less sensitive to effect a change in the initial clinical diagnosis or the subsequent therapeutic plan. (C) 2013 Baishideng Publishing Group Co., Limited. All rights reserved.